A legitimidade das realezas franca e visigótica nas obras de Gregório de Tours e Isidoro de Sevilha (séculos VI-VII) - Formentini, Luís Eduardo (2012)
In the fifth century, the Western Roman Empire disaggregated, giving place to various Germanic kingdoms. One of the main concerns of the rulers of these regni was the legitimating of their power, that is, to make their authority was recognized by the nobility and the population in general. This task showed itself challenging because of the following motives: first of all, these kingdoms were formed in locals that were, for centuries, ruled by Rome, and so the ways and symbols of imperial origin could not be ignored. Besides, most of these kingdoms suffered from a chronic internal instability. Moreover, there is the presence of the Eastern Roman Empire that, under Justinian, retook considerable areas of the Western Mediterranean. Due to this difficulties, the “barbarian” kings turned around to the Church, aiming a spiritual legitimacy to their power. The bishops saw the king as a powerful ally in their fight against the paganism and the heresies. Thereby, there was an approaching between king and episcopate, in which the bishops became important legitimators of the monarch’s authority. In the present dissertation, we will study the episcopal conceptions about the king and his functions in the works of two bishops: Gregory of Tours (538-594) and Isidore of Seville (560-636), who lived, respectively in Merovingian Gaul and in the catholic Visigothic Kingdom.